1994
DOI: 10.1139/b94-222
|View full text |Cite
|
Sign up to set email alerts
|

Direct absorption of water by hairy leaves of Phlomis fruticosa and its contribution to drought avoidance

Abstract: Water was sprayed on the adaxial surfaces of hairy and nonhairy leaves to study the possible significance of trichomes in dew or rainwater absorption. Plant species adapted to Mediterranean climate, experiencing periodic water shortage, were used. Water retention was higher and its duration significantly longer on hairy leaves, confirming visual observations in the field. Gravimetric measurements and fluorescence microscopy with the apoplasmic indicator Calcofluor showed that surface water quickly penetrated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
73
1
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(83 citation statements)
references
References 21 publications
4
73
1
5
Order By: Relevance
“…Hydrophilic hairs (in the typical sense) have been reported to cover the leaves of the Lady's Mantle (Alchemilla vulgaris); however, the underlying cuticle is hydrophobic, and in combination with the elastic properties of the hairs, the leaf is ultimately rendered water-repellent [6]. By contrast, the hydrophobic trichomes of the Jerusalem Sage (Phlomis fruticosa) are able to entrap and retain water droplets [25] but do not support a stable water film. These findings suggest that both the cuticular surface and the emergent trichomes need to be hydrophilic to allow the formation of stable water films as observed in H. nutans.…”
Section: Discussionmentioning
confidence: 99%
“…Hydrophilic hairs (in the typical sense) have been reported to cover the leaves of the Lady's Mantle (Alchemilla vulgaris); however, the underlying cuticle is hydrophobic, and in combination with the elastic properties of the hairs, the leaf is ultimately rendered water-repellent [6]. By contrast, the hydrophobic trichomes of the Jerusalem Sage (Phlomis fruticosa) are able to entrap and retain water droplets [25] but do not support a stable water film. These findings suggest that both the cuticular surface and the emergent trichomes need to be hydrophilic to allow the formation of stable water films as observed in H. nutans.…”
Section: Discussionmentioning
confidence: 99%
“…Benzing et al, 1976;Schlegel and Schönherr, 2002) and water in Bromeliads (e.g. Pierce et al, 2001;Reyes-García et al, 2012), the contribution of Phlomis fruticosa leaf trichomes to the absorption of water could not be clarified (Grammatikopoulos and Manetas, 1994). A traditional problem when investigating the mechanisms of foliar penetration is the occurrence of technical constraints associated with optical and fluorescence microscopy and attempting to observe the uptake of specific dyes and solutes by leaf surface micro-and nanostructures (Fernández and Eichert, 2009).…”
Section: Leaf Water Uptake and Ecophysiological Implicationsmentioning
confidence: 99%
“…The importance of trichomes and pubescent layers on water drop-plant surface interactions and on the subsequent potential water uptake into the organs has been analyzed in some investigations (Fahn, 1986;Brewer et al, 1991;Grammatikopoulos and Manetas, 1994;Brewer and Smith, 1997;Pierce et al, 2001;Kenzo et al, 2008;Fernández et al, 2011Fernández et al, , 2014Burrows et al, 2013). Trichomes are unicellular or multicellular and glandular or nonglandular appendages, which originate from epidermal cells only and develop outwards on the surface of plant organs (Werker, 2000).…”
mentioning
confidence: 99%
“…The presence of trichomes and aquaporins were essential in the absorption of water in Tillandsia ionantha plants (Ohrui et al, 2007;Maurel, 2001). Also the presence of trichomes facilitates the absorption of water and its influx in the mesophyll of leaves (Grammatikopoulos& Manetas, 1994). Some authors reported that the uptake by trichomes depends on its cutinization, which prevents the entry of the solutions in the cell (Burrows et al 2013).…”
Section: Trichomesmentioning
confidence: 99%